Is there a relationship between kinesiophobia, pain, depression, disease activity, functional status and quality of life in patients with ankylosing spondylitis? (Annals of Medical Research, 2023)
Aim: To evaluate the presence of kinesiophobia and its potential effects on pain, depression, disease activity and quality of life in patients with ankylosing spondylitis (AS).Materials and Methods: The study included 58 AS patients and 55 healthy controls. Tampa Kinesiophobia Scale (TKS) was used to evaluate the presence of kinesiophobia, Visual Analogue Scale (VAS) for severity of pain, Beck Depression Index (BDI) for depression level, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) for disease activity, Bath Ankylosing Spondylitis Functional Index (BAS-FI) for functional status, and Ankylosing Spondylitis Functional Index (ASQoL) for Quality of life.Results: In patient group, kinesiophobia rate was statistically significantly higher (68%) compared tothe healthy control subjects (27%) (p
Keywords: Ankylosing spondylitis; Kinesiophobia; Diseaseactivity; Pain; Quality of life